VIBRATION REDUCTION ON SINGLE-LINK FLEXIBLE MANIPULATOR USING H CONTROL - Saragih, Roberd; Tarwidi, Dede (Journal of the Indonesian Mathematical Society, 2008)
This paper is concerned with the vibration and position control of a single link flexible manipulator. Robot link manipulators are widely used in various industrial applications. It is desirable to build light weight flexible manipulators. Light flexible manipulators have a variety of applications, most significantly in space exploration,manufacturing automation, construction, mining, and hazardous operation. Timoshenko beam theory is used to derive mathematical model of a flexible manipulator. The dynamic equations of motion are obtained using the Lagrange's formulation of dynamics.The Hinfin; controller is designed for vibration and position control of the system. Simulations are presented and show that vibration and position control of a single flexible link can be controlled with the designed Hinfin; controller.DOI :Â http://dx.doi.org/10.22342/jims.14.2.52.73-82